Phylogeny, Diversity, Distribution, and Host Specificity of Haemoproteus spp. (Apicomplexa: Haemosporida: Haemoproteidae) of Palaearctic Tortoises - Javanbakht, Hossein; Kvičerová, Jana; Dvořáková, Nela; Mikulíček, Peter; Sharifi, Mozafar; Kautman, Matej; Maršíková, Aneta; Široký, Pavel (The Journal of eukaryotic microbiology, 2015)
A complex wide-range study on the haemoproteid parasites of chelonians was carried out for the first time. Altogether, 811 samples from four tortoise species from an extensive area between western Morocco and eastern Afghanistan and between Romania and southern Syria were studied by a combination of microscopic and molecular-genetic methods. Altogether 160 Haemoproteus-positive samples were gathered in the area between central Anatolia and eastern Afghanistan. According to variability in the cytochrome b gene, two monophyletic evolutionary lineages were distinguished; by means of microscopic analysis it was revealed that they corresponded to two previously described species-Haemoproteus anatolicum and Haemoproteus caucasica. Their distribution areas overlap only in a narrow strip along the Zagros Mts. range in Iran. This fact suggests the involvement of two different vector species with separated distribution. Nevertheless, no vectors were confirmed. According to phylogenetic analyses, H. caucasica represented a sister group to H. anatolicum, and both of them were most closely related to H. pacayae and H. peltocephali, described from South American river turtles. Four unique haplotypes were revealed in the population of H. caucasica, compared with seven haplotypes in H. anatolicum. Furthermore, H. caucasica was detected in two tortoise species, Testudo graeca and Testudo horsfieldii, providing evidence that Haemoproteus is not strictly host-specific to the tortoise host species.
Keywords: Animals; želvy; Testudo; cytochromy b; Barcoding; intraspecific variability; Protozoan Infections, Animal; cytochrome b; Molecular Sequence Data; Cytochromes b; Host Specificity; Phylogeny; molekulární sekvence - údaje; DNA, Protozoan; morphology; Haplotypes; protozoální DNA; protozoální infekce zvířat; Haemosporida; Leptoconops; Turtles; haplotypy; zvířata; fylogeneze; hostitelská specificita